Association of postural education and postural hygiene with low back pain in schoolchildren: Cross-sectional results from the PEPE study - Aina Maria Galmes-Panades; Pere Antoni Borràs; Josep Vidal-Conti (Tabriz University of Medical Sciences, 2023)
Background: Low back pain (LBP) is the leading cause of disability in the world that affects the population of all ages globally. The main aim of the present study was to analyze the cross-sectional association of postural education and postural hygiene habits with LBP, differentiating between frequency and intensity of pain. Methods: This cross-sectional study assessed 849 students aged 10-12 years from primary schools. The study was based on four different structured and self-administered questionnaires: back pain questionnaire, Back Pain and Body Posture Evaluation Instrument (BackPEI), Frequency of Commuting to and from School Questionnaire, and the Hebacaknow questionnaire. In addition, height and weight were included to determine the body mass index (BMI). Results: Participants with prevalence of LBP were significantly older (P=0.038), girls (P<0.001), taller (P=0.018), and practice active travelled back from school (P=0.016). Otherwise, participants with no prevalence of LBP sat correctly at the desk (P<0.001). Higher knowledge of postural education was associated with lower intensity of LBP (β=-0.07, CI=-0.12 - -0.02, P=0.004). Conclusion: The knowledge related to postural education it is associated with less LBP. School interventions improving knowledge about postural education, ergonomics and postural hygiene are needed to address this important matter.